A Mixed-Method Analysis of Entrepreneurship Training and Disaster Preparedness - Mufidatul Jariyah; Dini Prastyo Wijayanti; Marlita Dewi Lestari (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2025)
The study employed a mixed-methods design. In the quantitative phase, 60 vocational nursing students who had completed an entrepreneurship training module participated in a post-test survey using two validated Likert-scale instruments: one to assess entrepreneurial attitude and the other to measure disaster readiness. Simple linear regression and descriptive statistics were used in the analysis. Semi-structured interviews with ten carefully chosen students were conducted throughout the qualitative phase to investigate their learning experiences and perceptions. Thematic analysis was used to interpret the qualitative data. A regression research showed a significant positive link between entrepreneurial mentality and catastrophe readiness (R² = 0.314, β = 0.560, p < 0.01). The qualitative findings corroborated the statistical findings, with themes including greater crisis self-efficacy, proactive thinking, leadership attitude, and the perceived application of entrepreneurship to disaster circumstances. Entrepreneurial training helps nursing students prepare for disasters. The combination of quantitative indicators and student narratives provided a more in-depth knowledge of how entrepreneurial skills translate into disaster preparedness. The findings emphasize the need to incorporate innovation-driven approaches into nursing school curricula.